IMPLEMENTING YOUTUBE AS A MEDIUM FOR TODDLERS WITH AUTISTIC SPECTRUM DISORDER IN SECOND LANGUAGE ACQUISITION - Fitri, Qonita Maulana; Hamsia, Waode; Yunianti, Sofi (TELL - US JOURNAL, 2023)
Technological advancements are profoundly impacting education, particularly in the selection of learning media. Appropriate utilization of learning media can make learning easier and more effective. Language acquisition in children typically begins when they first begin to speak words independently. However, autistic children may struggle with acquiring new languages and demonstrating school readiness skills such as social, emotional, language, literacy, and executive functioning due to their individual social, communication, and behavioral presentations. This research aims to determine the implementation of YouTube as a medium for toddlers with autistic spectrum disorder in second language acquisition. The method used is qualitative with the instruments used are questionnaire, observation, and interview. The research subject was 5 autistic spectrum disorder (ASD) students at the Smart Kids School. The researchers did a questionnaire with 5 respondents as the parents of kindergarten students. The researchers also interviewed the teachers of the kindergarten. There were 5 questions to answer, which were described based on the respondents’ opinions. The research results show the process of implementing YouTube in English learning for autistic spectrum disorder students is appropriate and advantageous. Because YouTube provides exciting videos for children; they can hear the words spoken and see their physical appearance, which can aid comprehension. The children often imitate the dialogue of the characters they see on screen and their behavior. In addition, this research also showed that it is crucial for parents and teachers to monitor the content children watch on YouTube.